Topological configuration analysis and design for foam filled multi-cell tubes. (15th January 2018) - Sun, Guangyong; Liu, Tangyin; Huang, Xiaodong; Zhen, Gang; Li, Qing
Highlights: Established the FE model of foam filled multi-cell tubes coupled FEM and EFGM. Explored the effect of the different topological configurations on crashworthiness. Ranked the crashworthiness of foam filled multi-cell tubes with COPRAS. Conducted the topology optimization based on successive orthogonal arrays. Abstract: Foam filled multi-cell tubes have attracted much attention recently because of their exceptional advantages in energy absorption characteristics and lightweight. The study aims to explore the effects of cross-sectional configurations, including topological distribution of empty and foam-filler in the multi-cell tube, on the crashworthiness; and further optimizing the wall thickness and foam density. First, the coupled finite element method (FEM) and element free Galerkin method (EFGM) were adopted to model the foam filled multi-cell tubes. Second, the multi-criteria decision making method, namely COPRAS (complex proportional assessment), was used to rank the energy absorption characteristics of the considered foam filled multi-cell tubes with different topological configurations. The results show that the five-cell tube with four cells in the corners filled with forms was the best choice compared with the other topological configurations for the given design domain. Finally, the discrete optimization based on successive orthogonal arrays was employed to conduct the topological design of foam filled multi-cell tubes for maximizing the specific energy absorption ( SEA ) under the constraint of the global peak crushing force ( GPCF ). The results showed that the SEA of the optimized design is about 6.15% higher than the best choice from COPRAS analysis within the GPCF constraint, which demonstrated that the proposed approaches can be an effective tool for crashworthiness topology optimization of foam filled multi-cell tubes.